Integrating of web 2.0 technologies for interactive courseware : data structure and algorithm as case study - Mohd Nurhafeezi, Nordin (Universiti Malaysia Sarawak (UNIMAS), 2013)
Web 2.0 has received much attention in recent years due to its technology, which offer important education benefits. Web 2.0 is commonly associated with Web applications that facilitate interactive information sharing, interoperability, user-centred design, and collaboration utilizing of technology. Various technologies such as blogs, wikis, RSS, AJAX, Mashup and Tags help in supporting Web 2.0. It also has a greater potential for teaching and learning activities and how these technologies impact the education sector. The objectives of conducting this research are to determine the suitable design solution for courseware by comparing with existing courseware and to propose a framework for the project. Besides that, the research also aims to develop a prototype for Interactive Courseware using Web 2.0 by integrating Web 2.0 technologies and services and lastly to evaluate the effectiveness and the usability of the project by comparing the pre-test and post-test result and surnmative evaluation respectively. This project follows ADDIE model as guidelines and each phase are describe in detail in this report. The intention of the developed courseware is not to replace conventional class, but the develop courseware main objective is to assist students of FCSIT for better understanding towards Data Structure and Algorithms Course (TMC1433) through interactive delivering information.